2008
DOI: 10.1021/jp8024683
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Inelastic Scattering of OH Radicals from Reactive and Inert Liquid Surfaces

Abstract: The inelastic scattering of gas-phase OH radicals from a liquid hydrocarbon and a liquid perfluorinated polyether (PFPE) has been investigated. The surfaces examined were the potentially reactive, branched hydrocarbon squalane (C 30 H 62 , 2,6,10,15,19,23-hexamethyltetracosane) and the inert PFPE Krytox 1506 (F-[CF(CF 3 )-CF 2 O] 14ave -CF 2 CF 3 ). Superthermal OH was formed by 355-nm laser photolysis of a low pressure of HONO above the liquid surface. Laser-induced fluorescence (LIF) was used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
124
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(139 citation statements)
references
References 64 publications
14
124
1
Order By: Relevance
“…Due to gas-phase diffusion limitations the uncertainty in this measurement was relatively large, such that γ OH values ranging from 0.16 to 1.0 could not be ruled out. In addition, Bagot et al (2008) recently reported γ OH to be 0.49±0.04 for the reaction of superthermal OH on a squalane surface at low pressure. The slightly larger value for γ OH from this measurement is potentially due to the increased translational energy of the OH radicals resulting in a larger reaction probability.…”
Section: Resultsmentioning
confidence: 99%
“…Due to gas-phase diffusion limitations the uncertainty in this measurement was relatively large, such that γ OH values ranging from 0.16 to 1.0 could not be ruled out. In addition, Bagot et al (2008) recently reported γ OH to be 0.49±0.04 for the reaction of superthermal OH on a squalane surface at low pressure. The slightly larger value for γ OH from this measurement is potentially due to the increased translational energy of the OH radicals resulting in a larger reaction probability.…”
Section: Resultsmentioning
confidence: 99%
“…43,44,[46][47][48][49]62 A schematic of the revised apparatus is shown in Figure 1. It is a dual-chamber design, with the subsidiary, turbopumped chamber allowing SAM specimens to be stored rapidly under vacuum on removal from their solutions.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This conclusion was corroborated by our subsequent work on the inelastic scattering of OH radicals themselves from liquid surfaces. 62 We have also gone on to study the relative reactivity of O( 3 P) and OH-product energy partitioning for a range of different hydrocarbons. It is believed on the basis of molecular dynamics (MD) simulations 37,45,49,[63][64][65] that for squalane all three C-H bond types (primary, secondary, and tertiary) are available for abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the gas phase loss of OH they found that γ is greater than 0.1. Using a molecular beam scattering technique, Bagot et al 2008 measured an uptake coefficient of γ = 0.49 ± 0.04 by colliding superthermal OH radicals with a liquid squalane surface. 19 Rather than measuring the gas phase loss of OH, the reactive uptake coefficient can be quantified by monitoring the removal of an organic molecule in the particle phase.…”
Section: Introductionmentioning
confidence: 99%